Urinary N‐terminal pro‐brain natriuretic peptide: prognostic value in patients with acute chest pain. (6th April 2021) - Reynen, Stefanie; Schlossbauer, Michael; Hubauer, Ute; Hupf, Julian; Mohr, Arno; Orso, Evelyn; Zimmermann, Markus; Luchner, Andreas; Maier, Lars S.; Wallner, Stefan; Jungbauer, Carsten G.
Abstract: Aims: The objective of this study was to investigate the prognostic value of urinary N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) compared with plasma NT‐proBNP in patients presenting with acute chest pain in the emergency department. Methods and results: We measured simultaneously plasma and urinary NT‐proBNP at admission in 301 patients with acute chest pain. In our cohort, 174 patients suffered from acute coronary syndrome (ACS). A follow‐up (median of 55 months) was performed regarding the endpoints all‐cause mortality and major adverse cardiac events (mortality, congestive heart failure, ACS with the necessity of a coronary intervention, and stroke). Fifty‐four patients died during follow‐up; 98 suffered from the combined endpoint. A significant and positive correlation of urinary and plasma NT‐proBNP was found ( r  = 0.87, P  < 0.05). Patients with troponin positive ACS had significantly elevated levels of plasma and urinary NT‐proBNP compared with those with unstable angina pectoris or chest wall syndrome (each P  < 0.05). The highest levels of both biomarkers were found in patients with congestive heart failure (each P  < 0.05). According to Kaplan–Meier analysis, plasma and urinary NT‐proBNP were significant predictors for mortality and the combined endpoint in the whole study cohort and in the subgroup of patients with ACS (each P  < 0.05). Regarding Cox regression analysis, plasma and urinary NT‐proBNP were independent predictors for mortality and the combined endpoint (each P  < 0.05). Conclusions: Urinary NT‐proBNP seems to provide a significant predictive value regarding the endpoints all‐cause mortality and major adverse cardiac events in patients with acute chest pain and those with ACS.